1983
DOI: 10.1002/ijc.2910320604
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of malignant and non‐neoplastic cell phenotypes in highly malignant non‐Hodgkin lymphomas

Abstract: Malignant and non-neoplastic cells in 38 cases of highly malignant non-Hodgkin lymphomas: 3 centrocytic anaplastic, 18 centroblastic, 13 immunoblastic and 4 lymphoblastic (according to the Kiel classification) were immunophenotyped in cryosections and cell suspensions by means of monoclonal antibodies. Additionally, cell cycle analysis on cell suspensions was performed by DNA flow cytofluorometry. In 33 (87%) lymphomas the malignant cells expressed monoclonal surface immunoglobulin (Ig), which indicated B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Cytomorphological analyses Cytospins were prepared as described (Porwit‐Ksiazek et al , 1983). Briefly, cells were centrifuged on to slides and fixed in cold acetone or methanol.…”
mentioning
confidence: 99%
“…Cytomorphological analyses Cytospins were prepared as described (Porwit‐Ksiazek et al , 1983). Briefly, cells were centrifuged on to slides and fixed in cold acetone or methanol.…”
mentioning
confidence: 99%
“…It has long been recognized that T lymphocytes are consistently present in lymph nodes involved by B-cell non-Hodgkin's lymphomas (B-NHL), in close association with malignant cells (Habeshaw et al, 1983). Earlier studies indicated a favourable prognosis for B-cell lymphoma patients with a high content of tumour-infiltrating lymphocytes-T (TIL-T) and a high percentage of infiltrating CD8+ cytotoxic/suppressor cells (Porwit-Ksiazek et al, 1983;Lippman et aZ, 1990). Recent observations showing the clinical responsiveness of some lymphoma patients to interleukin-2 (IL-2) based immunotherapy suggested that antiturnour immune reactivity may be present in such patients (Weber et af, 1992).…”
mentioning
confidence: 99%